Cover Picture: Superelectrophilic Behavior of an Anion Demonstrated by the Spontaneous Binding of Noble Gases to [B12Cl11]− (Angew. Chem. Int. Ed. 27/2017). Issue 27 (9th June 2017) - Rohdenburg, Markus; Mayer, Martin; Grellmann, Max; Jenne, Carsten; Borrmann, Tobias; Kleemiss, Florian; Azov, Vladimir A.; Asmis, Knut R.; Grabowsky, Simon; Warneke, Jonas
Abstract : The molecular ion [B 12 Cl 11 ] − displays two seemingly incompatible sides, a negative and a positive one, just like the goddess Helja in Norse mythology. Physically, [B12 Cl11 ] − is an anion but it shows chemical reactivity known for highly electrophilic cations. In their Communication onpage 7980 ff., S. Grabowsky, J. Warneke et al. report that the electrophilicity of [B12 Cl11 ] − is so high that the noble gases Kr and Xe are bonded spontaneously at room temperature in a reaction that is typical of superelectrophiles.